Technical Efficiency of Smallholder Oil Palm Farms in Batanghari District Jambi Province, Indonesia - Chaira, Nabila; Rifin, Amzul; Rachmina, Dwi (Agro Bali : Agricultural Journal, 2024)
Smallholder oil palm farming is the main livelihood in Batanghari District, although its productivity has not shown maximum results. Maximum productivity achieved, it is necessary for farmers to do their business efficiently. This study aims to analyze technical efficiency and socio-economic factors that affect the technical efficiency of smallholder oil palm farming in Batanghari District. The research sample was determined using the multistage sampling method, which was used to sample farmers using simple random sampling. The number of respondents was 100 farmers. The stochastic frontier production function was used for data analysis. The results showed that the average technical efficiency of oil palm farming was 0,89 and had reached efficiency. However, this level can still be increased by 0,11 to achieve the highest level of technical efficiency. The technical efficiency of farming is affected by socio-economic factors, namely farming experience, distance from home to the farm, and the existence of partnerships. Based on the study's results, the technical efficiency of oil palm cultivation can be improved by utilizing production parameters precisely and accurately and increasing farmers' resources to achieve maximum production. For sustainable agricultural development, further research is needed to analyze the economic efficiency of oil palm farming so that the overall picture of both technical and economic efficiency can be seen.